ON THE PERSUASIVE SUBSTANCE OF RUSSIAN VERB - LAMBARJYAN, SRBUHI (Bulletin of Yerevan University H: Russian Philology, 2019)
The article is devoted to analising of persuasive semantic component in the meaning structure of the Russian verb. The research shows that Russian verbs have persuasive component, which expresses in emotional, mental verbs and “verbs – communications”. The author considers several classes of Russian verbs and shows that some of them expresses persuasive meaning directly and others indirectly.
Keywords: persuasivennes, emoional and mental aspects of communication